Miesto želdynų problemos ir jų socialinė paskirtis - Jakovlevas-Mateckis, Konstantinas (Journal of Architecture and Urbanism, 2006)
Problems of urban green areas and their social function The town is a complicated system the main components of which are the community and its environment. Therefore, town planning and formation of green area should be performed taking into consideration the community’s activities and needs. Favorable conditions must be created for people to live, work, study and rest. Solving these social tasks a great role falls on urban public areas and green areas. The town’s community, municipality and investors have to take an active part in solving this task. Urban green areas have to be formed systematically. In this system we can distinguish three groups of green areas which are very important for the community: a natural frame, green areas for territories of a general use (parks, town gardens, squares, etc), and green areas integrated into territories of various purposes (dwelling, industrial and commercial activities, learning, etc). They have to be planned and formed taking into account the activities and needs of the local community. The author’s analysis shows that there are a lot of gaps in this sphere. In order to eliminate its shortcomings, it is necessary to pass a law regulating urban green areas as soon as possible, and on this basis to prepare rules and normative standards for green area planning, paying a great attention to the social function of green areas. Article in Lithuanian. Santrauka. Nagrinėjama miesto raida ir želdynų vieta jo struktūroje. Vadovaujantis subalansuotos plėtros koncepcija pagrindžiama miesto želdynų sistemis˘kumo būtinybė ir sistemos socialinis pagrįstumas. Pateikiama nauja miesto želdynų sistemos samprata, nurodoma, kad jos pagrindą sudaro miesto gamtinis karkasas ir dvi miesto želdynų teritorijų grupės: atskirųjų želdynų grupė ir į kitos paskirties žemių teritorijas integruotų želdynų, sistemoje atliekančių antraeilį vaidmenį, grupė. Detaliau nagrinėjami integruoti želdynai gyvenamosiose teritorijose, kuriose jie atlieka labai svarbų socialinį vaidmenį. Reikšminiai žodžiai: socialinė miesto želdynų paskirtis, žmogaus veikla ir poreikiai; miesto želdynų sistema; gamtinis karkasas; atskirieji bendro naudojimo želdynai; integruotieji želdynai; miesto želdynų įstatymas ir normos. First Published Online: 21 May 2013